Effect of nutrient sources and weed control measures on quality and yield of baby corn (Zea mays) - Barod, Niranjan Kumar; Dhar, Shiva; Kumar, Ashok; Das, Dilip Ranjan (Annals of Agricultural Research, 2016)
A field experiment was conducted during kharif season of 2008 at the Experimental Farm of Division of Agronomy, Indian Agricultural Research Institute, New Delhi. The study was planned to assess the effect of nutrient sources and weed control measures on yield and quality of baby corn. The significantly higher husked and dehusked cob yields (4.43 t/ha and 2.15 t/ha, respectively) were obtained with the application of N through vermicompost as compared to N applied through leaf compost, FYM and fertilizer. Significantly higher protein and sugar concentration were also obtained with the application of N through vermicompost. In case of weed control measures, the highest husked and dehusked cob yield (4.29 t/ha and 2.18 t/ha respectively) and maximum concentration of protein and sugar was recorded in weed free treatment which was at par with two hand weeding at 20 and 40 days after sowing (DAS) or pre emergence application of tank mixed atrazine @ 0.5 kg and pendimethalin @ 0.75 kg/ha.